Building Resilience and Planning for Extreme Water-Related Events - Sprague, Teresa; Prenger-Berninghoff, Kathrin (Palgrave Studies in Climate Resilient Societies,, 2019)
This book discusses what it means for cities to work toward and achieve resilience in the face of climate change. The content takes an urban planning perspective with a water-related focus, exploring the continued global and local efforts in improving disaster risk management within the water sphere. Chapters examine four cities in the US and Germany - San Francisco, San Diego, Solingen and Wuppertal - as the core case studies of the discussion. The chapters for each case delve into the current status of the cities and issues resilience must overcome, and then explore solutions and key takeaways learned from the implementation of various resilience approaches. The book concludes with a summary of cross-cutting themes, best-practice examples and a reflection on the relevance of the approaches to cases in the wider developing world. This book engages both practitioners and scientific audiences alike, particularly those interested in issues addressed bythe Sendai Framework for Disaster Risk Reduction 2015-2030, the 2030 Agenda for Sustainable Development, the recent Water Action Decade 2018-2028 and the Rockefeller Foundation's 100 Resilient Cities.